The Effect of Emotional Exhaustion and Emotional Labor on Cargo Employees' Turnover Intentions and Job Satisfaction - konyalılar, Nil; Halıcı, Ali (International Journal of Contemporary Economics and Administrative Sciences, 2025)
The main purpose of the study is to examine the effect of the emotional labor of cargo company employees on emotional exhaustion, job satisfaction, and turnover intention. Cargo company employees have a labor-intensive job design. Therefore, they may encounter many physical and mental difficulties in their jobs. The study also evaluates whether employees' expressions of their emotions during the work process are a precursor to explaining turnover intention, job satisfaction, and emotional exhaustion. Quantitative research method is used in the study. The survey technique is used as the data collection method. Data was collected from a total of 247 cargo employees in the study. Data were analyzed in the Smart PLS statistical program. Accordingly, frequency, variety, and surface acting have positive effects, and deep acting has negative effects on emotional labor. On the other hand, intensity does not affect emotional labor. In addition, emotional labor has a negative effect on job satisfaction, but it does not affect turnover intention. Finally, job satisfaction does not affect turnover intention.